Analisis Kesediaan Menerima Pembayaran Jasa Lingkungan Air Masyarakat Sekitar Taman Hutan Raya Wan Abdul Rachman (Tahura War) : Studi Di Desa Sumber Agung Kecamatan Kemiling Kota Bandar Lampung - Roni Febri Kurniawan; Slamet Budi Yuwono; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
One approach to conservation efforts on forest that has been converted to mixed farms in Tahura WAR which is also the upstream of DAS Way Betung is the application of Payment for Environmental Services (PES)of water. The value of water PES alleged to approach the value of the willingness to accept (WTA) payment to the upstream society as a provider environmental services. The purpose of this study was to determine the magnitude of the WTA from DAS Way Betung society especially water services and the factors that influence it, in addition to know the form of incentives that the public wants. The method used in this study is the analysis of Willingness to Accept (WTA), regression analysis and qualitative descriptive analysis. This research is held on April 2014 at Sumber Agung village, Kemiling, Bandar Lampung city. Based on the results obtained by the analysis of the value of the average WTA respondent is Rp 4,358.33 /tree/year. If the total number of trees on public land is 10,475 whole tree, then the total value of the WTA obtained is Rp 44,935,750.00/year. Factors that significantly affect the value of the WTA is the level of education, land area, and the number of trees. Form of incentives other than money the public wants is a fertilizer aid, rural development like transportation infrastucture, and help seed. Keywords: DAS Way Betung, payment for environmental service, WTA